2021
DOI: 10.1021/acsomega.1c00679
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Pyrene-Adorned Imidazolium Salts with Multicolor Solid-State Fluorescence: Synthesis, Structure, Photophysical Properties, and Application on the Detection of Latent Fingerprints

Abstract: New water-soluble acetylpyrene-bound imidazolium salts (1- N -methyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 1 ), 1- N -isopropyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 2 ), 1- N -allyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 3 ), and 1- N -isopropyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium hexafluorophosphate ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…For most of the known pyrene derivatives, it has been reported that these exhibited mechanoflorochromism (MFC) and polymorphism as a result of changes in molecular packing in the crystal structure. 5,18,[48][49][50] So, we decided to study the effects of mechanical grinding on the newly synthesized derivative of pyrene-thiophene (PyS-Y). Many MFC materials transform from crystalline to amorphous under mechanical pressure due to the defects in the crystal packing, and revert to its original structure when heating the ground product or after fuming it with solvents.…”
Section: Resultsmentioning
confidence: 99%
“…For most of the known pyrene derivatives, it has been reported that these exhibited mechanoflorochromism (MFC) and polymorphism as a result of changes in molecular packing in the crystal structure. 5,18,[48][49][50] So, we decided to study the effects of mechanical grinding on the newly synthesized derivative of pyrene-thiophene (PyS-Y). Many MFC materials transform from crystalline to amorphous under mechanical pressure due to the defects in the crystal packing, and revert to its original structure when heating the ground product or after fuming it with solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary/Pilot studies – Several compounds were presented as new dusting powders: AIE-active composites or molecules [ [277] , [278] , [279] , [280] , [281] ], algal biomass [ 282 ], anti-perovskite phosphors [ 283 ], azo-dyes [ 284 ], β-cyclodextrin-berberine complexes [ 285 ], benzazole derivatives [ 286 ], bisamide analogues [ 287 ], cadmium-doped silica microspheres [ 288 ], chitosan-tripolyphosphate-lysine conjugates [ 289 ], coumarin–pyridone conjugates [ 290 ], crushed eggshells and clamshells [ 291 ], crushed gambir [ 292 ], curcumin analogues [ 293 ], doped montmorillonite [ 278 , 294 , 295 ], doped starch microspheres [ [296] , [297] , [298] ], europium-dextrose composites [ 299 ], iron oxide/zinc sulphide hybrid [ 300 ], metal-organic frameworks [ 301 ], organic NIR emitters [ 302 , 303 ], perylenetetracarboxylate compounds [ 304 ], phenylthiazoles [ 305 ], phosphor-cellulose hybrids [ 306 ], pyrazoles [ 307 ], pyrene-tagged imidazolium salts [ 308 ], pyridine and pyrimidine derivatives [ 309 , 310 ], rare-earth-doped phosphors [ [311] , [312] , [313] , [314] , [315] , [316] , [317] , [318] , [319] ], reduced graphene oxides [ 320 ], resveratrol powder [ 321 ], rhodamine B-doped diatomaceous earth [ 322 ], Schiff base complexes [ [323] , [324] , [325] ], talcum powder […”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…p-p interactions upon crystallization, thus enhancing the solid-state emission. 7 Finally, the third feature, which is extremely useful for the technological application of these compounds, is based on the combination of strong push-pull intramolecular electronic effect. Joining electron-donating and electron-withdrawing components into a p-conjugated structure allows control over the Highest-Occupied Molecular Orbital (HOMO) and Lowest-Unoccupied Molecular Orbital (LUMO) energy levels.…”
Section: One Molecule To Light It Allmentioning
confidence: 99%